Safety and Efficacy of Endovascular Embolization of Ruptured Intracranial Aneurysms within 72 hours of Subarachnoid Hemorrhage - Li, Xin-Yu; Li, Cong-Hui; Wang, Ji-Wei; Liu, Jian-Feng; Li, Hui; Gao, Bu-Lang (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Purpose The purpose of the study was to investigate the safety and efficacy of endovascular embolization of ruptured intracranial aneurysms within 72 hours of subarachnoid hemorrhage (SAH).Materials and Methods Patients with intracranial aneurysms treated with embolization were divided into group A (n = 277), patients with ruptured aneurysms treated within 72 hours of SAH; group B (n = 138), patients with ruptured aneurysms treated beyond 72 hours; and group C (n = 93), patients with unruptured aneurysms.Results Embolization was successful in all but four patients (99.2%). The periprocedural complication rate was 36.2% in group B, significantly (p < 0.05) greater than that in group A (24.5%) or group C (11.8%). The rebleeding rate was 9.7% (6/62 patients) in groups A and B after embolization and only 0.3% (1/346 patients) in aneurysms with total or subtotal occlusion. Of these three groups of patients, 69.7% in group A, 58.7% in group B, and 76.3% in group C achieved Glasgow Outcome Scale (GOS) score of 5 or modified Rankin Scale (mRS) score of 0– to 1 at discharge. A significant difference (p < 0.05) existed in the clinical outcome between the three groups. The percentages of patients without deficits (GOS 5 or mRS 0–1) and slight disability (mRS 2) were 80.2% in group A, 81.2% in group B, and 96.7% in group C. The mortality rate was 4.3% (12/277 patients) in group A and 7.2% (10/138 patients) in group B with no significant (p = 0.21) difference. Follow-up was performed at 3 to 54 months (mean 23.2), and the recanalization rate was 28.6% (32/112 patients) in group A, 22.4% (11/49 patients) in group B, and 28.6% (16/56 patients) in group C, with no significant differences (p = 0.15). Hydrocephalus occurred in 30.5% (39/128 patients) in group B, which was significantly (p < 0.01) greater than that in group A (9.4%) or group C (2.2%).Conclusion Early embolization of ruptured cerebral aneurysms within 72 hours of rupture is safe and effective and can significantly decrease periprocedural complications compared with management beyond 72 hours. Timely management of cisternal and ventricular blood can reduce hydrocephalus incidence and improve prognosis.
Keywords: intracranial aneurysms; endovascular embolization; subarachnoid hemorrhage; complications; effect